Why programs fail a guide to systematic debugging - Zeller, Andreas (Amsterdam ; Boston : Elsevier/Morgan Kaufmann ; Heidelberg : Dpunkt.verlag, 2006)
Why Programs Fail is about bugs in computer programs, how to find them, how to reproduce them, and how to fix them in such a way that they do not occur anymore. This is the first comprehensive book on systematic debugging and covers a wide range of tools and techniques ranging from hands-on observation to fully automated diagnoses, and includes instructions for building automated debuggers. This discussion is built upon a solid theory of how failures occur, rather than relying on seat-of-the-pants techniques, which are of little help with large software systems or to those learning to program. The author, Andreas Zeller, is well known in the programming community for creating the GNU Data Display Debugger (DDD), a tool that visualizes the data structures of a program while it is running. * Winner of a 2006 Jolt Productivity Award for Technical Books * Shows how to reproduce software failures faithfully, how to isolate what is important about the failure, and to discover what caused it * Describes how to fix the program in the best possible way, and shows how to create your own automated debugging tools * Includes exercises and extensive references for further study, and a companion website with source code for all examples and additional debugging resources.
About the Author; Preface; 1 How Failures Come to Be; 2 Tracking Problems; 3 Making Programs Fail; 4 Reproducing Problems; 5 Simplifying Problems; 6 Scientific Debugging; 7 Deducing Errors; 8 Observing Facts; 9 Tracking Origins; 10 Asserting Expectations; 11 Detecting Anomalies; 12 Causes and Effects; 13 Isolating Failure Causes; 14 Isolating Cause-Effect Chains; 15 Fixing the Defect; Appendix: Formal Definitions; Glossary; Bibliography; Index.
Includes bibliographical references (p. 429-438) and index.
Keywords: Debugging in computer science; Electronic books